Therapy with Bone-Seeking Radiopharmaceuticals in Patients with Skeletal Metastases Beyond Simple Palliation of Bone Pain - Mariani, Giuliano (Onkologische Welt, 2011)
Bone metastases account for most of the morbidity and deterioration in the quality of life experienced by patients with various types of solid cancers, and occur in about 65–70% of the cases with advanced breast or prostate cancer. Clinical management of metastatic bone pain includes several options (1, 2) to be employed either alone or in varying combinations. One step further in this direction is a multicenter trial exploring the anti-tumour therapeutic potential of the association between 153Sm-EDTMP (Quadramet®) and Docetaxel in patients with hormone-refractory prostate cancer with predominant bone metastases.